The beneficial impact of silicon on wheat drought resilience is dependent on cultivar and stress intensity - Shaw, Katie; Thorne, Sarah; Chapman, Caroline; Fleming, Andrew; Hartley, Susan; Gray, Julie (Frontiers in Plant Science, 2025)
Drought has a major impact on crop yields. Silicon (Si) application has been proposed to improve drought resilience via several mechanisms including modifying the level of stomatal gas exchange. However, the impact of Si on transpiration and stomatal conductance varies between studies. We assessed the impact of supplemental Si on wheat water use and drought resilience in two high Si accumulating genotypes that vary in stomatal density and stomatal conductance. These genotypes varied considerably in their responses to Si treatment and short-term severe drought at the booting stage of development. For example, gas exchange measurements revealed that one genotype (H5) showed a significant increase in stomatal conductance with Si treatment, but the other genotype (H3) did not. Application of Si increased yield 3.5-fold in the H5 higher stomatal density genotype following the severe drought but Si had no yield-effect on the H3 lower stomatal density genotype. To determine whether differences in stomatal density could account for these differing Si responses, a modern cultivar, Fielder, was grown alongside a reduced stomatal density mutant, TaEPF1OE. Gas exchange measurements again showed that Si had no impact on the stomatal conductance of the lower stomatal density genotype, TaEPF1OE, but did increase stomatal conductance in the Fielder background. This is in line with the results from H3 and H5, suggesting that stomatal density plays an important role in the impact of Si treatment on stomatal function. However, following severe drought, Si increased yields in both the TaEPF1OE stomatal density mutant and the Fielder background, indicating that stomatal density alone does not account for genotype-specific yield responses seen in H3 and H5. Next, two genotypes that showed yield improvements with Si under short-term severe drought stress (Fielder and H5) were subjected to a longer-term vegetative drought stress. Here, Si had minimal effects on stomatal conductance, water use or biomass, suggesting that the impact of Si on drought resilience is strongly affected by drought type and duration. We conclude that for Si fertilization to be used as an effective drought mitigation strategy, crop cultivar, together with drought intensity and duration, must be considered.